Post Partum Death in a Patient Diagnosed With COVID-19 - Sivevski, Atanas; Karadzova, Dafina; Davceva, Natasha; Aleksioska-Papestiev, Irena; Kadriu, Romir; Velickovic, Ivan; Markovic, Ivana; Pejcic, Nada; Baysinger, Curtis L. (Frontiers in Global Women's Health, 2020)
Background: There are few case reports describing maternal mortality and intensive care of the pregnant patient with COVID-19 infection. Case: A 27-year-old patient at 34 weeks of gestation was admitted for the evaluation of cough, fever, tachypnea, and oligohydramnios. The day of admission she underwent cesarean delivery for a non-reassuring fetal heart rate tracing. Over the next 6 days her clinical condition deteriorated, she developed multi organ system failure, and died despite aggressive supportive care. Conclusion: Although mortality related to COVID-19 in pregnancy has been rarely reported to date, we describe a case of progressive clinical deterioration postpartum despite aggressive supportive care. Management strategies specific for pregnant women have not been developed. In timing delivery, the obstetrician must consider the possibility that the inflammatory response associated with CD may increase the risk for multiorgan system failure in parturients with COVID-19 while recognizing that risks to the fetus may be higher in patients with COVID-19 than in other critically ill parturients. Vertical transmission of infection to the neonate did not occur in our case and has not been demonstrated in other pregnancies with COVID-19 disease.